A apologia de Paulo na Segunda Carta aos Coríntios: uma análise retórica - Ribeiro, Joelma Batista dos Santos (2010)
The present dissertation focuses on the field research of Text and Discourse in the Oral and Written Modalities. Its goal is to investigate the constitution of the rhetorical proves: ethos, pathos and logos in the theological discourse, due the fluency of such a discourse in our society. We present a panoramic view of the history of Bible canonization and its process of translations of the New and the Old Testaments. We have selected as a sample for analyzes the chapters 10, 11, 12 and 13 of the Second Letter of Paul to the Corinthians, text which forms Paul s apology. In order to help this analyzes, we have done a presentation of Paul s Biography as well as of the city of Corinth and its Christian community. We have also written about the general characteristics of Paul s writings, dedicating a special attention to the Second Letter to the Corinthians, source of our sample of analyzes. To achieve the established objective, we used the theories of Classic Rhetoric and The New Rhetoric from Michel Meyer (1993, 1994, 2007), Chaïm Perelman and Lucie Olbrechts-Tyteca (1996). We have started the analyses rescuing some of the historical, linguistics and theological aspects of Paul and the Corinthians community and looked for each one of the rhetorical proves methodologically separated. The analyses proved the argumentation within Paul s discourse is made up by the rhetorical proves that are intertwined and superposed with one each other, which goal is to conquer the audience